ATENÇÃO À QUALIDADE DE VIDA: FORTALECIMENTO E VALORIZAÇÃO DA MEMÓRIA DE IDOSOS - Montandon de Araújo Souza, Leandro; de Sousa Oliveira, Maria Aparecida; Lima de Morais, Leidiane Cristina (Intercursos, 2025)
Não consta